Implementation of mobile augmented reality on physics learning in junior high school students - Rahmat, Anggi Datiatur; Kuswanto, Heru; Wilujeng, Insih; Perdana, Riki (Journal of Education and e-Learning Research, 2023)
Technology has an essential role in the educational field. Technology-based mobile has the potential to improve education through Augmented Reality (AR). This study investigates the effect of mobile augmented reality on physics learning achievement and students' opinions on using this technology. The study used a convergent parallel pattern from mixed-method models in which quantitative and qualitative data are collected simultaneously and analyzed independently. The study participants are 64 (7th-grade students) who are learning solar system concepts at one of the junior high schools in West Java Province, Indonesia. This study collects pre- and post-test data as quantitative data to analyze students' learning achievement using the normalized gain score. The result showed that the students using mobile augmented reality have higher criteria for learning achievement than those using textbooks. The qualitative data was collected from interviewed students after using mobile augmented reality and analyzing using descriptive analysis. The results of the student opinion state that augmented reality is a new learning environment that effectively helps them understand physics concepts, enhances students' learning achievement and helps concretize abstract concepts through visual 3D simulations. Moreover, according to the study, students find it easier to understand physics concepts after using mobile augmented reality.